2015
DOI: 10.1167/iovs.15-17335
|View full text |Cite
|
Sign up to set email alerts
|

Skewness of Fractional Anisotropy Detects Decreased White Matter Integrity Resulting From Acute Optic Neuritis

Abstract: Citation: Goodyear BG, Zayed NMH, Cortese F, Trufyn J, Costello F. Skewness of fractional anisotropy detects decreased white matter integrity resulting from acute optic neuritis. Invest Ophthalmol Vis Sci. 2015;56:7597-7603. DOI:10.1167/ iovs.15-17335 PURPOSE. Diffusion tensor imaging (DTI) has demonstrated optic nerve damage associated with optic neuritis (ON); however, the usefulness of mean fractional anisotropy (FA) specifically is varied in the literature. We wished to determine whether histogram ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…RD seems to have enhanced discriminatory value compared to FA for detecting the effects of ON within the visual system ( Figure 3B ). Within the optic nerve, a significant increase of RD was found for eleven out of sixteen performed comparisons, with five resulting from acute ON ( 27 , 28 , 103 , 104 ) and six from remote ON ( 25 , 26 , 103 , 109 ), though the ratio of significance was higher for acute ON. When assessing their ON patient group with a wide range of time from onset (median of 4.0 years since the first instance of ON), Naismith and colleagues [2010] ( 26 ) reported that they were able to distinguish the affected optic nerve from the unaffected optic nerve based on RD, while also differentiating between severity of visual outcomes (mild to severe).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…RD seems to have enhanced discriminatory value compared to FA for detecting the effects of ON within the visual system ( Figure 3B ). Within the optic nerve, a significant increase of RD was found for eleven out of sixteen performed comparisons, with five resulting from acute ON ( 27 , 28 , 103 , 104 ) and six from remote ON ( 25 , 26 , 103 , 109 ), though the ratio of significance was higher for acute ON. When assessing their ON patient group with a wide range of time from onset (median of 4.0 years since the first instance of ON), Naismith and colleagues [2010] ( 26 ) reported that they were able to distinguish the affected optic nerve from the unaffected optic nerve based on RD, while also differentiating between severity of visual outcomes (mild to severe).…”
Section: Resultsmentioning
confidence: 92%
“…For remote ON, RD within the optic nerve also correlates with RNFLT, contrast sensitivity, visual acuity, and the visually evoked potential latency and amplitude ( 25 , 26 , 109 ). Not all results showed a simple increase of RD within the optic nerve, with Goodyear and colleagues [2015] ( 28 ) finding that RD within the bilateral optic nerve decreased immediately after ON and increased back to a normal level after 6 months. Interestingly, Nguyen and colleagues [2022] ( 111 ) discovered a non-linear trend where RD within the affected optic nerve was less than the unaffected nerve at baseline, whilst it yielded higher RD values 3 months after ON onset, a relationship which still persisted 12 months after onset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the fractional anisotropy value, the higher the anisotropy is. Fractional anisotropy can also indicate the injury and repair of white matter associated with ON, facilitating the detection of white matter [27]. DTI value is closely related to visual dysfunction of visual evoked potentials in patients with multiple sclerosis-ON [28].…”
Section: Tips Pertaining To Pathophysiological Informationmentioning
confidence: 99%
“…For example, Yankeelov et al ( 2007 ) acquired dynamic contrast enhancement and ADC maps in a study of breast cancer, created ADC histograms and looked for statistically significant changes in individual bin frequency between pre- and post-treatment histograms. Goodyear et al ( 2015 ) studied changes in optic nerve mean MD, FA, axial (AD), and radial diffusivity (RD) as well as changes in histogram skewness of those quantities in optic neuritis patients. Wagner et al ( 2016 ) characterized pediatric cerebellar tumors using the 25th percentile, 75th percentile, and skewness of FA, MD, AD), and RD.…”
Section: Introductionmentioning
confidence: 99%